Adapting Management Control Systems to Organizational Contingency Factors: A Study of Moroccan Industrial Companies - Hind Hammouch; Otilia Manta; Maria Palazzo (Businesses)
This study investigates how organizational contingency factors, namely company size, environmental uncertainty, technological capacity, and organizational structure, affect the design and effectiveness of management control systems (MCS) in Moroccan industrial companies. Drawing on contingency theory, which emphasizes the alignment of organizational systems with contextual factors, this research applies quantitative methods to a sample of 190 industrial firms in Morocco, achieving a 76% response rate to the distributed surveys. The data are analyzed using correlation and linear regression techniques to explore these relationships. The findings reveal that larger firms, those operating in dynamic and uncertain environments, and those with advanced technological systems tend to implement more sophisticated, integrated, and participative MCS. Furthermore, flexible and decentralized organizational structures significantly enhance the adoption of adaptive control systems. These results underscore the importance of tailoring MCS to organizational characteristics and environmental conditions, particularly in emerging market contexts. This study’s novel contribution lies in its application of contingency theory to a non-Western industrial context, addressing a gap in the literature by demonstrating how specific regional factors influence MCS practices. This research offers practical insights for Moroccan industrial firms seeking to improve their operational efficiency, adaptability, and strategic decision making in volatile markets.